Tributação no Estado Social e Democrático de Direito: finalidade, motivo e motivação das normas tributárias - Barros, Maurício (2010)
The purpose of this thesis is to encourage a reading of the Brazilian tax system from the Federal Constitution of 1988 and Brazil s condition as a true social and democratic legal state, the objectives and bases of which should have effects on all fiscal activity (in the broad sense), from the establishment and exercise of tax authority to the proper use of the funds collected. The methodological basis is Friedrich Müller s structuring theory of law, in which aspects of reality (the normative framework) are compositional factors of legal rules, together with the textual data or normative program. There must therefore be a dialogue between law and reality, breaking with the is and should be dichotomy that is typical of formalism. This thesis will systematically analyze the constitutional tax system (broadly speaking), in comparison with the other terms of the Brazilian Constitution, seeking to promote the conformation of legal tax rules to the condition of a social and democratic legal state and to the economic intervention of the Brazilian Constitution, electing the tax constitutional motive as the given that goes beyond the limiting concept of tax authority and takes in the purpose and cause of taxation, as a point of support for the exercise of the tax power. That position carries certain consequences with it, such as the (re)configuration of the constitutional suppositions for the institution of taxes, their adaptation to the constitutional finalities and social needs, the legal treatment to be given to the misuse of the product of taxation, the need for motivation and the importance of the effectiveness of the taxation rules, in accordance with the purposes stated in the Brazilian Constitution. This thesis will also propose a new classification of tax authority, focused on the specific purpose of each type of tax and on the constitutional motive for its institution/change, and that the paradigm of the optional exercise of tax authority be broken with and the requirement (mandatory) of taxes according to (a) the specific purpose of each type of tax, (b) its conformation with reality and (c) the proper use of the product of the collection for the constitutionally determine finalities